APLIKASI COMMODITY SYSTEM ASSESSMENT METHOD (CSAM) DALAM DISTRIBUSI KUBIS (Brassica oleraceae var. capitata) DARI PETANI DI KECAMATAN PETANG KE PENGECER. - Budiastra, I Gede; Lani Triani, I.G.A; Hartiati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 5 No 1 (2017): Maret)
The purpose of this research was to determine the number of distribution channels cabbage (Brassica oleracea Var Capitata) of farmers to retailers in Petang district, knowing the type of distribution channels and postharvest handling of cabbage from farmers to retailers in Petang district, knowing the impact of postharvest losses and the value of the damage of farmers to retailers Petang district. The method used in this research is survey method with the application of the Commodity Systems Assessment Method in the form of questionnaires distributed to farmers, collectors, wholesalers, suppliers and retailers of cabbage. In the distribution of cabbage, there are four lines, namely, lanes 1 farmers ? retailers, lane II farmers ? collectors ? retailers, lane III farmers ? collectors ? wholesalers ? retailers, lines IV farmers ? collectors ? wholesalers ? suppliers ? supermarkets. Post-harvest handling at the farm level include harvesting, sorting and cleaning, packaging and transportation. Post-harvest handling at the level of collectors, and wholesalers include weighing, sorting, and transporting, postharvest handling at the retail level covering inspection, packaging, and display, postharvest handling at the level of suppliers includes weighing, sorting, packaging and transportation, postharvest handling level includes supermarkets weighing, inspection, and display. Impact on cabbage postharvest losses at the farm level, namely the significant harvest reached 7.57%, at the level of the collectors in the transport process is insignificant reached 2.68%, at the level of big traders are not significant when transporting reached 3.8%, at the retail level in sorting no significant sidak reached 2.38%, in the sorting supplier significant level of 11.8%. Keyword : CSAM, distribution channels, postharvest , cabbage.
Keywords: 125,